Persalinan Pervaginam dan Menyusui sebagai Faktor Risiko Kejadian HIV pada Bayi - Dewi Astri Purnaningtyas; Julian Dewantiningrum (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTVaginal delivery and breastfeeding as risk factors of HIV in infantsBackground: HIV incidence is increasing among housewives, leading to increasing HIV in infants. The aim of this study was to identify risk factors of HIV in infants.Method: A case control study was carried out among women who visited VCT (voluntary counselling and testing) clinic RSUP Dr. Kariadi during 2003-2011 that fulfill the inclusion criteria of term delivery and babies infection confirmed by VCT or PCRDNA/RNA. Risk factors were assessed by interview about ARV consumption during pregnancy, mode of delivery, prophylactic ARV for neonates and breastfeeding. CD4 concentration before delivery was defined from medical report. All subject divided into two group based on HIV infected children status, HIV and non HIV. Analysis used bivariate analysis using Chi square and odd ratio.Result: From 28 women: 16 women in HIV group and 12 women in non HIV group. Breast feeding (OR 13.00; 95% CI 2.12-79.59, p=0.006) and vaginal delivery (OR 6.07; 95% CI 1.11-3.24, p=0.050) were the most important risk factors for HIV infection in infants. ARV consumption during pregnancy (OR 0.13; 95% CI 0.01-1.40), ARV prophylactic in neonates (OR 0.20; 95% CI 0.02- 2.23), CD4 >400 sel/mm3 before delivery (OR 0.33; 95% CI 0.03-4.019) were not risk factors. Conclusion: Vaginal delivery and breastfeeding were risk factor for the incidence of HIV-infected infants.Keywords: Vertical transmission HIV, CD4 concentration, mode of delivery, breastfeeding, ARVABSTRAKLatar belakang: Insiden penderita HIV meningkat pada ibu rumah tangga, yang akan mempengaruhi peningkatan insiden penderita HIV baru pada masa perinatal. Penelitian ini bertujuan ingin mengetahui berbagai faktor risiko yang berpengaruh terhadap kejadian HIV pada bayi.Metode: Desain penelitian adalah studi kasus kontrol. Subyek penelitian adalah ibu dengan HIV yang datang ke klinik VCT RSUP Dr. Kariadi tahun 2002-2011, dengan kriteria inklusi cukup bulan serta bayi telah dilakukan pemeriksaan PCR DNA/RNA. Data diperoleh lewat wawancara langsung maupun per telepon dengan kuesioner terbuka dan pemeriksaan CD4 menjelang persalinan. Wawancara untuk mencari faktor risiko pemberian ARV selama kehamilan meliputi cara persalinan, pemberian ARV profilaksispada bayi dan pemberian ASI. Data dianalisis dengan Chi square.Hasil: Sebanyak 28 subyek penelitian terbagi dalam kelompok HIV 16 subyek dan non HIV 12 subyek. Analisis berbagai faktor risiko menunjukkan bahwa pemberian ASI (OR 13,00, 95% CI 2,12-79,59) dan persalinan pervaginam (OR 6,07, 95% CI 1,11-3,24) merupakan faktor risiko yang berpengaruh terhadap kejadian HIV pada bayi. Nilai CD4 serum ibu >400 sel/mm3 menjelang persalinan (OR 0,33; 95% CI 0,03-4,019), pemberian ARV profilaksis neonatus (OR 0,20; 95% CI 0,02-2,23) dan pemberian ARVpada ibu hamil (OR 0,13, 95% CI 0,01-1,40), tidak merupakan determinan terhadap penularan HIV dari ibu ke janin.Kesimpulan: Persalinan pervaginam dan pemberian ASI merupakan faktor risiko kejadian HIV pada bayi.